2008
DOI: 10.4081/jlimnol.2008.93
|View full text |Cite
|
Sign up to set email alerts
|

Diel vertical migration patterns in two populations of Chaoborus flavicans larvae (Diptera: Chaoboridae) in response to fish kairomones

Abstract: Diel vertical migration (DVM)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
4
7
0
Order By: Relevance
“…Obvious peak abundance was sometimes observed at depth during the day, whereas at night, the peak was much less obvious and occurred in the subsurface. Two different patterns of nighttime distribution have been observed in previous studies, with a clear peak abundance of Chaoborus larvae reported at the surface layer (Lagergren et al 2008) or at the subsurface layer (Stahl 1966;Teraguchi and Northcote 1966;Lagergren et al 2008;Oda and Hanazato 2008) in accordance with the results of our study. Lagergren et al (2008) found that night distribution changed seasonally and argued that slight changes in light intensity, even during the night, might influence distribution.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Obvious peak abundance was sometimes observed at depth during the day, whereas at night, the peak was much less obvious and occurred in the subsurface. Two different patterns of nighttime distribution have been observed in previous studies, with a clear peak abundance of Chaoborus larvae reported at the surface layer (Lagergren et al 2008) or at the subsurface layer (Stahl 1966;Teraguchi and Northcote 1966;Lagergren et al 2008;Oda and Hanazato 2008) in accordance with the results of our study. Lagergren et al (2008) found that night distribution changed seasonally and argued that slight changes in light intensity, even during the night, might influence distribution.…”
Section: Discussionsupporting
confidence: 94%
“…Although the deep anoxic water layer that develops in summer can be an effective refuge from fish predation (Irvine 1997;Voss and Mumm 1999), it disappears in winter, and so the bottom sediments become an alternative refuge during the cold season. The observed pattern of DVM in winter is consistent with findings from field studies in different lakes (Goldspink and Scott 1971;Haney et al 1990; Dawidowicz, Pijanowska and Ciechomski (1990) c Tjossem (1990), the fishless and fish ponds in the Cornell University Experimental Pond Facility d Oda and Hanazato (2008), NIES: experimental pond at the National Institute for Environmental Studies, Japan Lorke et al 2004), which documented the DVM of Chaoborus larvae in all seasons, including winter, although the adaptive significance was not discussed in these studies. Voss and Mumm (1999) and Gliwicz et al (2000) found Chaoborus larvae in the bottom sediments, and not in the water column, throughout the day during winter (i.e., overwintering).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This trend could be mainly due to lower risk of visual predation by fish (Lampert, 1993;Saether, 1997). They also showed the normal pattern of DVM in the water column, down during the day and up at night, as described in the literature for Chaoborus flavicans from fish-abundant lakes (Gliwicz et al, 2000;Oda and Hanazato, 2008). However, the highest number of larvae in July was recorded during the day.…”
Section: Biotic Factors and Microcrustacean Diel Vertical Migrationsupporting
confidence: 78%
“…Chaoborus sp. may also migrate to surface waters during the night when visual predation is least, to exploit the abundant zooplankton resource (Ringelberg, 1999;Rejas et al, 2007;Oda & Hanazato, 2008). The high numbers of Chaoborus sp.…”
Section: Discussionmentioning
confidence: 99%